Prioritising Sexual and Reproductive Health on a Female Inpatient Psychiatric Ward: A Quality Improvement Project - Eleanor Mitham; Katherine Wickham; Elizabeth Pillai; Stella Rosson; Miranda Holliday (BJPsych Open, 2025)
Aims: Serious mental illness is associated with higher rates of sexual assault and gynaecological cancers, alongside pre-menstrual disorders and the menopause which can be implicated in psychiatric presentation, relapse or treatment resistance. This project aimed to ensure better screening and referral for sexual and reproductive health issues in order to improve relevant health outcomes.